Users' Satisfaction with Service Quality of Nutribid Application During the COVID-19 Pandemic - Rihla Syamila Az Zahra Zahra; Eka Andriani; Al Mukhlas Fikri; Mu-Yeh Kuo (Universitas Negeri Malang, 2022)
During the COVID-19 pandemic, nutritional problems are observed to be increasing, such as obesity, minimum nutritious food intake, and micronutrient deficiency. The dreadful effects of COVID-19 on the health sectors, combined with the advanced technology development, had prompted the emergence of Nutribid application. Nutribid is an online health service application focusing on nutritional health. This study aimed to investigate the users' satisfaction with the service quality of Nutribid application during the COVID-19 pandemic. This quantitative research approach used the descriptive method. The univariate test was used to analyze the data through mean and frequency distribution. The users' satisfaction was examined from 5 aspects, namely responsiveness, empathy, reliability, tangibles, and assurances. We obtained scores of 86.32, 88.8, 88.84, 87.84, and 88.52 percent for responsiveness, empathy, reliability, tangibles, and assurances, respectively. These scores indicate that the users present great satisfaction with the services from Nutribid. This result is also supported by the average results of the Likert scale of more than 81 percent. Our findings can be used as a reference for user satisfaction with the services of the Nutribid application.